Polymicrobial Prosthetic Joint Infections: Unraveling Risk Factors and Outcomes in a Single-Center Study - Álvaro Auñón; Ignacio Ortiz; Salvador Peñarrubia; Carmen Álvaro; Estíbaliz Torrecilla-Sádaba; Joaquin Garcia-Cañete; Jaime Esteban (Microorganisms, 2025)
Periprosthetic joint infection (PJI) is a serious complication after joint arthroplasty, with polymicrobial PJIs representing a distinct subset associated with worse outcomes. This study aims to characterize the risk factors, microbiological profiles, and clinical outcomes of polymicrobial PJIs in a single tertiary care center. A retrospective analysis was conducted on 499 patients diagnosed with PJI between 2010 and 2023. Polymicrobial infection was defined by isolation of ≥2 distinct pathogens from intraoperative samples. Demographic, microbiological, and clinical data were analyzed. Treatment success was defined as infection eradication without recurrence or chronic suppressive therapy. Polymicrobial PJIs accounted for 18.2% of cases. Patients with polymicrobial infections had higher rates of obesity, insulin-dependent diabetes, and higher Charlson comorbidity scores. Coagulase-negative staphylococci and gram-negative bacilli were more frequently isolated in polymicrobial infections, while S. aureus predominated in monomicrobial cases. Treatment success rates were significantly lower in polymicrobial infections, both in acute (61.5% vs. 94.5%, p = 0.003) and chronic settings (51.3% vs. 75.3%, p = 0.02). Polymicrobial PJIs are associated with distinct microbiological patterns, increased comorbidity burden, and significantly worse clinical outcomes. Recognition of specific risk factors and pathogen profiles is essential to optimize management strategies for this complex condition.